Potential lesson from a model-based exploration on treatment effect heterogeneity of mal de débarquement syndrome - Maruta, Jun; Yakushin, Sergei B.; Cho, Catherine (Frontiers in Neurology, 2025)
BackgroundA central vestibular neural mechanism known as velocity storage may be inappropriately conditioned in mal de débarquement syndrome (MdDS), a rare chronic vestibular disorder with a continuous false sensation of self-motion described as non-spinning vertigo. Visual-vestibular therapy approaches designed to recondition the three-dimensional properties of velocity storage have yielded much clinical success, but not without limitations. An alternative therapeutic approach, designed to attenuate the contribution of malfunctioning velocity storage in higher-order neural processing, has also yielded positive results, but at a lower success rate. We sought a possible explanation for the latter shortcoming using a mathematical model.MethodsThe three-dimensional orientation properties of velocity storage can be modeled as a dynamical system using a 3 × 3 system matrix. For normal upright, the system matrix is diagonal, with its eigenvectors aligning with the head-fixed roll, pitch, and yaw axes, and the yaw eigenvector with gravity. A pull sensation of MdDS has been expressed with a system matrix with off-diagonal elements representing cross-axis coupling and interpreted as a misalignment between the yaw eigenvector and the head vertical. We manipulated the velocity storage’s yaw time constant and output weight.ResultsThe model predicted that attenuating the velocity storage contribution could exaggerate the pull sensation.ConclusionThe present model-based exploration points to a possible weakness in the MdDS treatment approach focused on velocity storage attenuation, while likely beneficial otherwise. When a pulling sensation is present, the treatment protocol may need to be supplemented with another approach that specifically counters this problem, such as optokinetic stimulation.